PENGARUH KREDIT USAHA RAKYAT (KUR), PENYERAPAN TENAGA KERJA DAN LAMA USAHA TERHADAP PENDAPATAN PENERIMA KUR DI KECAMATAN DENPASAR TIMUR - devi, nia chintya; Saskara, IdaAyu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
MSMEs have an important existence because they are supporters of the national economy (Adebayo and Moshood, 2014). Realizing the huge role of MSMEs in the national and regional economy, especially in Denpasar City, it is natural to get greater attention to the existence of MSMEs, especially in strengthening the people's economy in Bali Province. Thus, it is hoped that the provision of People's Business Credit (KUR) can increase the income of business actors. Other benefits, it is hoped that business production will increase and job opportunities will also be wider. This study aims to analyze 1) the effect of People's Business Credit (KUR) on the income of KUR recipients, 2) the effect of labor absorption on the income of KUR recipients, 3) the effect of length of business on the income of KUR recipients in East Denpasar District. This study uses primary data for KUR recipients in East Denpasar District. The data were then analyzed by multiple linear regression analysis. The results of the analysis show that there is a positive and significant effect of KUR on the income of KUR recipients in East Denpasar District. There is a positive and significant effect of length of business on the income of KUR recipients in East Denpasar District. There is a positive and significant effect of employment on the income of KUR recipients in East Denpasar District. There is an effect of KUR, length of business, and absorption of labor together on the income of KUR recipients in East Denpasar District.